An improved digital watermarking algorithm using combination of least significant bit (LSB) and inverse bit - Abdullah Bamatraf, Abdullah Omar (2012)
Software watermarking is one of the most important methods for protecting copyrights and authenticating ownership; which can be used to prevent software piracy. In order to provide high quality watermarked image, the watermarked image should be imperceptible. Least significant bit (LSB) is a technique that has been used for digital watermarking. Many researchers have improved LSB to embed watermark in the image. In this thesis, we introduce an improved digital watermarking algorithm using least significant bit (LSB). This method is chosen due to its minimal effect on the image. LSB is used by inversing the binary values of the watermark text and shifting the watermark according to the odd or even number of pixel coordinates of image before embedding the watermark. The proposed algorithm can be personalized according to the length of the watermark text. If the length of the watermark text is more than ((M*N)/8)-2 (where M*N is the amount of pixels in the image), the proposed algorithm will also embed the extra of the watermark text in the second LSB. We compare our proposed algorithm with the 1-LSB algorithm and Lee’s algorithm and Yang's algorithm using Peak signalto-noise ratio (PSNR). The value of the watermarked dock image is 54.5691 dB which is higher than the traditional LSB 53.6950 dB and Lee's algorithm 53.7041 db and Yang's algorithm 52.4518 dB. Also in the other image, the proposed algorithm got the highest value of PSNR. This improved algorithm improved its quality of the watermarked image. We also attack the watermarked image by using cropping and adding noise and we got good results as well